Pohjois-Atlantin värähtelyn vaikutus Suomen talvilämpötiloihin ja sademäärään - Kanerva, Kyösti (Helsingfors universitet, 2016)
There has been considerable variation in Finnish winter conditions during the last decade. Especially in Southern Finland, where some winters have been warm, rainy and snowless. On the other hand there have been winters with freezing temperatures and extensive snow cover, even in southern parts of Finland. The North Atlantic Oscillation (NAO) is the most prominent and important form of climate variability in Europe. It has been previously shown to cause considerable variations to advection of heat and moisture between Atlantic Ocean and adjacent continents, notably during winter. The first objective of this study is to find out if there is dependence between NAO and winter climate indicators in Finland. Secondly, it aims to quantify the variations in mean temperature, mean maximum temperature and mean minimum temperature and precipitation caused by the changes in strength and phase of the NAO. In addition, the regional variability in correlation, in variance explained by the NAO and effects on temperatures and precipitation within Finland is studied. The dependence between NAO-index and temperatures and precipitation in Finland is studied by using correlation analysis. Regression analysis is used to find out how much variation in temperatures and precipitation can be explained by variations in the NAO-index. Furthermore, it estimates the magnitude of change in temperatures and precipitation. The results show that NAO affects temperatures and precipitation in Finland during winter months. There is, however, a notable spatial variation in the effect between Southern and Northern Finland. The effect of NAO on precipitation is smaller and shows greater variation than with temperatures. The findings of this study are in agreement with earlier studies. The phase of the North Atlantic Oscillation affects the properties of the air masses flowing towards Finland and the winter conditions. This study finds that winter temperatures in Finland are more dependent on large scale atmospheric circulation and its variability ...